The long-run returns to public agricultural R&D in South Africa: evidence from an updated TFP Series (1950–2023) - Molokoli, Poloko John (Stellenbosch : Stellenbosch University, 2026)
Thesis (MScAgric)--Stellenbosch University, 2026.